(untitled) - Ransome, Stafford (London and NewYork, 1899)
There are three distinct Japans in existence side by side to day -- the old Japan, which has not wholly died out; the new Japan, which as yet has hardly been born, except in the spirit; and the transition Japan, which is passing through its most critical throes just now
Keywords: Japan,Nhật Bản; History,Lịch sử